ADVANCED RESEARCH METHODOLOGY EMPOWERMENT WORKSHOP FOR FACULTY MEMBERS VIA A WEBINAR ORGANIZED BY CV. ADIBAAISHA AMIRA: A STRATEGIC INITIATIVE FOR ACADEMIC EXCELLENCE - Abdul Rosid (Adiba Aisha Amira, 2023)
This advanced research methodology empowerment workshop is hosted via webinar by CV. Adiba Aisha Amira represents a strategic initiative to foster academic excellence among faculty members. The workshop is meticulously designed to address the evolving needs of contemporary research in a dynamic academic landscape. Through comprehensive sessions, the workshop delves into crucial areas such as research design and methodology, data analysis techniques, and scholarly writing and publication strategies. Participants will benefit from the expertise of distinguished resource persons and facilitators, ensuring a well-rounded exploration of advanced research principles. Emphasizing participant engagement, the workshop incorporates interactive learning activities, including case studies, practical examples, group discussions, and peer learning, creating a vibrant community of scholars. The webinar's logistical aspects, from the chosen platform to the registration process, are optimized for a user-friendly and inclusive experience. This initiative reflects a commitment to equipping faculty members with the requisite skills and insights to navigate the complexities of advanced research, ultimately contributing to enhancing academic excellence within their respective institutions.